The Racial Formation of Asian American Non-Profit Work in Orange County, California. (22nd November 2022) - Hom, Laureen D.
Abstract: This article examines how a distinct racialized identity of Asian Americans is asserted through the work of ethnic non-profit organizations in Orange County, California. This area is home to the third-largest Asian American population in the United States but also has historically been seen as a suburban region with limited infrastructure to support ethnic communities. Using a regional racial formation theory framework, this study shows how diversity has been integral to understanding the Asian American identity, but that the regional context matters in how we define this pan-ethnic identity and its diversity. This narrative of diversity expressed by non-profit organization community leaders contribute to a re-articulation of an Asian American identity that underscores the distinct mix of Asian ethnic groups that contrasts with older urban immigrant gateways; challenges the model minority stereotype through mental health and anti-Asian discrimination advocacy; and emphasizes place and issue-based work that extends beyond their ethnic communities. The findings highlight how Asian American non-profit work provides lessons for broadly addressing diversity, equity, and inclusion in public administration practice.